Fusões e aquisições cross-border: uma análise do efeito provocado por fatores culturais e de mercado no desempenho econômico-financeiro - Martins, Rayana Kelly Brasileiro (2019)
This research had as main objective to analyze the effect that the cultural distance and the peculiarities of market provoke in the economic-financial performance of the companies involved in cross-border mergers and acquisitions processes. The sample consisted of 111 cross-border mergers and acquisitions in the Brazilian market during the period from 2011 to 2016. The survey data were collected from the Thomson Reuters database. In order to capture the effects of cultural distance and market peculiarities on economic and financial performance, the regression model was used with panel data by fixed effects and random effects. In all, two panels were constructed, with about 888 observations for each model variable. From the obtained results it was possible to observe that both the cultural distance and the geographic distance did not present statistically significant values sufficient to infer its influence in the economic-financial performance. However, the positive coefficient of both variables is indicative that a greater cultural and geographical distance would be associated with a higher performance of the companies. In addition, it was found that the level of indebtedness and companies considered to be negatively related to performance and cashfinanced operations produced a positive impact on corporate performance. The evidence indicated that size was an important determinant for the performance of the companies considered in the research. It was also observed that the level of development of the countries also did not report statistically significant values, and it is not possible to confirm their influence on the performance obtained after the merger. On the other hand, the performance tended to be higher when one observes higher level of corporate governance and positive exchange rate effect. With regard to business freedom and commercial freedom, the results were inconclusive and no evidence was found that a greater volume of market capitalization impacts the performance of companies. In this way, it is possible to emphasize that cultural distance and the level of market development do not justify international investment patterns and that possible variations in post-merger performance can be explained by factors commonly explored in the literature, such as size, indebtedness, governance performance and exchange variation, as well as other factors not considered in this research.